Evaluating photosynthetic models and their potency in assessing plant responses to changing oxygen concentrations: a comparative analysis of An–Ca and An–Ci curves in Lolium perenne and Triticum aestivum - Ye, Zi-Piao; Yang, Xiao-Long; Ye, Zi-Wu-Yin; An, Ting; Duan, Shi-Hua; Kang, Hua-Jing; Wang, Fu-Biao (Frontiers in Plant Science, 2025)
Accurate determination of photosynthetic parameters is essential for understanding how plants respond to environmental changes. In this study, we evaluated the performance of the Farquhar-von Caemmerer-Berry (FvCB) model and introduced a novel model to fit photosynthetic rates against ambient CO2 concentration (An–Ca) and intercellular CO2 concentration (An–Ci) curves for Lolium perenne and Triticum aestivum under 2% and 21% O2 conditions. We observed significant discrepancies in the FvCB model’s fitting capacity for An–Ca and An–Ca curves across different oxygen regimes, particularly in estimates of key parameters such as the maximum carboxylation rate (Vcmax), the day respiratory rate (Rday), and the maximum electron transport rate for carbon assimilation (JA-max). Notably, under 2% and 21% O2 conditions, the values of Vcmax and Rday derived from An–Ca curves using the FvCB model were 46.98%, 44.37%, 46.63%, and 37.66% lower than those from An–Ci curves for L. perenne, and 47.10%, 44.30%, 47.03%, and 37.36% lower for T. aestivum, respectively. These results highlight that the FvCB model yields significantly different Vcmax and Rday values when fitting An–Ca versus An–Ci curves for these two C3 plants. In contrast, the novel model demonstrated superior fitting capabilities for both An–Ca and An–Ci curves under 2% and 21% O2 conditions, achieving high determination coefficients (R2≥ 0.989). Key parameters such as the maximum net photosynthetic rate (Amax) and the CO2 compensation point (Γ) in the presence of Rday, showed no significant differences across oxygen concentrations. However, the apparent photorespiratory rate (Rpa0) and photorespiratory rate (Rp0) derived from An–Ci curves consistently exceeded those from An–Ca curves for both plant species. Furthermore, Rpa0 values derived from An–Ca curves closely matched observed values, suggesting that An–Ca curves more accurately reflect the physiological state of plants, particularly for estimating photorespiratory rates. This study underscores the importance of selecting appropriate CO2-response curves to investigate plant photosynthesis and photorespiration under diverse environmental conditions, thereby ensuring a more accurate understanding of plant responses to changing environments